2004
DOI: 10.1016/j.febslet.2004.04.056
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of a glucosyltransferase catalyzing glucosylation of curcumin in cultured Catharanthus roseus cells

Abstract: Catharanthus roseus cell suspension cultures are capable of converting exogenously supplied curcumin to various glucosides. The glucosylation efficiency is enhanced by addition of methyl jasmonate (MJ) to the cultures prior to curcumin administration. Two cDNAs encoding UDP-glucosyltransferases (CaUGT1 and CaUGT2) were isolated from a cDNA library of cultured C. roseus cells, using a PCR method directed at the conserved UDP-binding domain of plant glycosyltransferases. The sequence identity between their deduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…A number of ginsenosides can be produced by this reaction, and it has been previously reported that there are 35 kinds of ginsenosides in P. ginseng . Unfortunately, the mechanism by which a variety of structures can be produced has yet to be clearly elucidated, although the characterization of genes encoding glucosyltransferase has been documented from several plants (Meesapyodsuk et al 2007;Kaminaga et al 2004;Achnine et al 2005). This may be the result of the innumerable glucosyltransferases encoded in a plant.…”
Section: Resultsmentioning
confidence: 96%
“…A number of ginsenosides can be produced by this reaction, and it has been previously reported that there are 35 kinds of ginsenosides in P. ginseng . Unfortunately, the mechanism by which a variety of structures can be produced has yet to be clearly elucidated, although the characterization of genes encoding glucosyltransferase has been documented from several plants (Meesapyodsuk et al 2007;Kaminaga et al 2004;Achnine et al 2005). This may be the result of the innumerable glucosyltransferases encoded in a plant.…”
Section: Resultsmentioning
confidence: 96%
“…CaUGT2 cDNA was cloned from C. roseus as described previously [23] and UGT73C6 was isolated from Arabidopsis thaliana by RT-PCR, based on the sequence retrieved from the DNA database (Accession no. AAD20155 [At2g36790]).…”
Section: Cdna Clonesmentioning
confidence: 99%
“…PSPGs in the database but not identical to the UGTs previously isolated from periwinkle (Kaminaga et al, 2004;Masada et al, 2009). Using these partial cDNA fragments, we obtained two full-length cDNAs by 59-rapid amplification of cDNA ends (RACE) and designated them as periwinkle UGT6 and UGT7.…”
Section: Molecular Cloning Of Ugts From Periwinkle Cell Cultures and mentioning
confidence: 99%